The Effectiveness of the Boarding School-Based Islamic Education Model in Shaping Student Character - Anugrah, Ruri Liana (Al-Ashri: Ilmu-Ilmu Keislaman, 2025)
Character education is an integral and very important part of education in Indonesia and is considered important because it can be a means of shaping good behavior. Therefore, good overall education management is needed in terms of the intellectual, technical, psychological, social, moral, and religious aspects of students. This study aims to determine the effectiveness of the Islamic education model based on boarding schools in shaping the character of students, which has been implemented at the junior high school level in one of the schools in Indonesia. This study uses a qualitative method with data sources obtained through observation, interviews, and documentation. Data analysis was carried out by interpreting the data that had been successfully collected, and conclusions were drawn from this interpretation. Data validity was examined using triangulation methods, namely by seeking the same data sources through various data collection techniques. The results of this study indicate that: i) Boarding school programs in Islamic secondary schools consistently reinforce positive values and provide opportunities for students to practice and apply these values in their daily lives, which can have a greater impact on character building. ii) The effectiveness of character building in schools does not depend solely on the school itself. The involvement and support of parents, the commitment of teachers, and the individual efforts of students also play an important role in shaping the character development of students.